Advancing service automation technology in tourism for sustainable development goals: a review and agenda for theories, contexts, methodologies and actions - Yong, Rachel Yuen May; Chua, Bee Lia; Han, Heesup; Fakfare, Pipatpong (Routledge, 2025)
Service automation technologies (SAT) can transform tourism structures by boosting industry competitiveness and meeting evolving tourist needs. SAT can support the United Nations sustainable development goals when they are effectively leverage. This review considers the impact of SAT via 173 tourism studies using the Stepwise Tri-Stage Assessment and Reporting for Systematic Literature Reviews (STAR-SLR) protocol in its inaugural application, which was designed in order to optimize the review process. We also propose the theory, context, methodology and action (TCMA) framework as an agenda-setting tool, advocating for continuous and actionable strategies to harness SAT’s potential for a sustainable future by 2050.